Fungsi Ruang Terbuka di Sekitar Kawasan Rumah Susun: Studi Kasus pada Rumah Susun Bendungan Hilir 1 - Yosica Mariana (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The presence of a building, whether large or small, brings impacts on the environment. Residential houses, commercial buildings, office buildings or flats have both positive and negative impacts. This research aims to determine the changing function and utilization patterns of open green spaces in the some areas around a flat into built spaces. Rumah susun Bendungan Hilir 1 is purposively selected as the study site. The research method uses a descriptive survey is to make direct field observations. Based on the results it is showed that there is a land use change, especially in some areas directly adjacent to the flats, and a deviation on Spatial Plan as well as on the open space.